Osteoarthritis of the hands and muscle strengthening exercises: an integrative update and review of the literature - Souza,Isabelle Ferreira da Silva (2018)
ABSTRACT BACKGROUND AND OBJECTIVES: Osteoarthritis of the hands is a highly prevalent disease that can lead to significant deformity and disability. The therapeutic approach in the management of osteoarthritis of the hands is based on pharmacological and non-pharmacological approaches. However, none of these treatments demonstrated a reduction of joint damage, and it presents itself in a purely symptomatic way. Yet, expert practitioners strongly recommend and use hand muscle strengthening in patients with hand osteoarthritis, but there is no consensus for such conduct. The objective of the study was to review the concepts about hand osteoarthritis as well as to bring the current evidence on muscle strengthening as a non-pharmacological treatment for this disease. CONTENTS: The study reviewed the United States National Library of Medicine database (Pubmed). The words used were: hand osteoarthritis, exercises, physiotherapy and rehabilitation. We included 5 articles in English, published in the last 10 years, focused on muscle strengthening exercises for osteoarthritis patients. CONCLUSION: There is no consensus, nor a more effective exercise protocol, although exercises and physiotherapy are still recommended. We suggest conducting randomized controlled clinical trials to improve the evidence on this subject.